Nationwide Lockdown, Population Density, and Financial Distress Brings Inadequacy to Manage COVID-19: Leading the Services Sector into the Trajectory of Global Depression - Donglei Yu; Muhammad Khalid Anser; Michael Yao-Ping Peng; Abdelmohsen A. Nassani; Sameh E. Askar; Khalid Zaman; Abdul Rashid Abdul Aziz; Muhammad Moinuddin Qazi Abro; Sasmoko; Mohd Khata Jabor (MDPI, 2024)
Indexed by WOS/SCOPUS